2013
DOI: 10.1007/s00213-013-3152-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sub-chronic donepezil on brain Abeta and cognition in a mouse model of Alzheimer’s disease

Abstract: These results suggest that the observed cognitive improvement produced by donepezil in Alzheimer's disease may be due, at least in part, to reduction of brain Aβ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…The F1-hybrid strain was a crossing of heterozygous hAPP V717I males in C57Bl/6J background with wild-type FVB/N females, and double transgenic mice overexpressing hAPP Lon and hPS1 A246E were generated by cross-breeding the single hAPP Lon mutant with homozygous hPS1 A246E mice [ 30 ]. The age-dependent behavioural and histopathological phenotype of double transgenic hAPP Lon /hPS1 A246E mice has been reported previously [ 30 , 37 , 41 ]. All hAPP Lon /hPS1 A246E mice were genotyped by two independent PCR assays with primers specific for the mutant hAPP and hPS1 sequence on DNA extracts from tail biopsies sampled at the age of three weeks and three weeks before treatment start, respectively.…”
Section: Methodsmentioning
confidence: 57%
“…The F1-hybrid strain was a crossing of heterozygous hAPP V717I males in C57Bl/6J background with wild-type FVB/N females, and double transgenic mice overexpressing hAPP Lon and hPS1 A246E were generated by cross-breeding the single hAPP Lon mutant with homozygous hPS1 A246E mice [ 30 ]. The age-dependent behavioural and histopathological phenotype of double transgenic hAPP Lon /hPS1 A246E mice has been reported previously [ 30 , 37 , 41 ]. All hAPP Lon /hPS1 A246E mice were genotyped by two independent PCR assays with primers specific for the mutant hAPP and hPS1 sequence on DNA extracts from tail biopsies sampled at the age of three weeks and three weeks before treatment start, respectively.…”
Section: Methodsmentioning
confidence: 57%
“…Among the different approaches tried, the inhibition of AChE is the most successful one (30). To date, AChE inhibitors are widely used to improve the cognitive impairments such as learning and memory ones in patients with Alzheimer’s disease through enhance acetylcholine levels at synapses where the neurotransmitter has been evacuated in order to degeneration of neuronal cells (31). …”
Section: Discussionmentioning
confidence: 99%
“…Donepezil at the dose of 2 mg/kg once a day for five consecutive days for two weeks improve spatial learning and memory deficits following traumatic brain injury independent of its effects on neurogenesis (16). Moreover, after treatment with donepezil a considerable improvement of memory as well as a dose-dependent depletion of amyloid-β (Aβ) was observed in brain of hAPP/PS1 mice (31). In gerbils, administratation donepezil at the dose of 5 mg/kg for 21 consecutive days reduced hippocampal neuro-degeneration and cognitive impairments after global cerebral ischemia (32).…”
Section: Discussionmentioning
confidence: 99%
“…By and large, DON has shown to reverse scopolamine-induced learning deficits in reference and working memory tests in rodents [ 57 , 20 , 58 ]. Interestingly, a study performed in transgenic AD mice revealed that sub-chronic administration of DON for 2 weeks concomitantly improved the cognitive deficits along with the dose-dependent decrease of brain soluble and insoluble Aβ40 and 42 [ 59 ]. Consistent with preclinical studies, DON has been shown to counteract the negative impact of SD on cognitive function in a group of healthy individuals whose cognitive performance was greatly impaired by SD [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%